The relationship between postural stability, core muscle endurance and agility in professional basketball players (Annals of Medical Research, 2021)
Aim: The purpose of this study was to identify relationships between postural stability, core muscle endurance and agility in basketball players.Materials and Methods: 21 professional male basketball players [age: 17.±0.63 (years), body weight: 78.69±9.22 (kg), height: 186±7 (cm), BMI: 22.72±2.26 (kg/cm²)] were included to this study. Three balance variables were measured using Biodex Biosway™. Core muscle endurance was measured using three core endurance tests proposed by Mcgill. Agility was assessed by Hexagonal Obstacle Test (HOT).Results: The analysis results showed that postural stability is associated with HOT (r: 0.457). In addition, the postural stability was related to extension muscle endurance test and side bridge test (respectively, r: -0.501 and r: -0.468). There is no correlation between HOT and core muscle endurance test in basketball players. Conclusion: The athletes with good postural stability were better core muscle endurance and agility. It is important to apply exercise programs that enhance postural stability and increase core muscle endurance to improve sportive success.